Effect of Composition and Dielectric Properties for (YBCO) Superconductor Compound in Different Preparation Methods - Haider, Haider M.J.; Jasim, Kareem A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
The superconductor compound (YBa2Cu2.8Zn0.2O7+Î´) is prepared by solid state reaction (SSR), Sol-gel (SG) and laser Pulse deposition (PLD) methods. We used the X-ray diffraction technique, which shows an orthorhombic crystalline system for all the samples, and increase in the high-phase (Y-123) and decrease in low-phase and vary in proportion according to the method of preparation with the emergence of some impurities. The behavior of the samples in terms of electrical resistance and critical temperature was investigated all samples showed superconducting behavior. The properties of the dielectric (real dielectric constant, imaginary dielectric constant, loss tangent, alternating electrical conductivity) were studied as a function of frequency and range (50 Hz-1MHz) at room temperature. The results are demonstrate the apparent change in the dielectric properties by using the method of preparation of laser pulse deposition PLD at the expense of other methods, Microscopic images of the samples were examined at very high magnitudes through the scanning electron microscopy (SEM). In addition to using the titration method to determine the proportion of oxygen.